On the incorporation effect of the ring‐junction heteroatom. The sEDA(III) and pEDA(III) Descriptors. (22nd December 2014) - Mazurek, Andrzej; Dobrowolski, Jan Cz.
Abstract : Descriptors of the heteroatom incorporation effect in the ring‐junction position, sEDA(III) and pEDA(III), are introduced for the first time. They express the change in the σ and π valence electron population produced by the heteroatom. The sEDA(III) descriptor is a good measure of electronegativity of ring‐junction incorporants. Unexpectedly, the pEDA(III) descriptor does not correlate with π‐electron characteristics because the 'aromatic' bond pattern in the considered fused ring systems depends on the incorporants' change within the group or period of the periodic system. We found that the HOMA aromaticity index of conjugated paths is useful to trace π‐electron flows in heteroatom‐incorporated polycyclic (aromatic) systems. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Descriptors of the heteroatom incorporation effect in the ring‐junction position, sEDA(III) and pEDA(III), are introduced. They express change in the σ and π valence electron population produced by the heteroatom.